2023
DOI: 10.2196/41344
|View full text |Cite
|
Sign up to set email alerts
|

Functional Requirements for Medical Data Integration into Knowledge Management Environments: Requirements Elicitation Approach Based on Systematic Literature Analysis

Abstract: Background In patient care, data are historically generated and stored in heterogeneous databases that are domain specific and often noninteroperable or isolated. As the amount of health data increases, the number of isolated data silos is also expected to grow, limiting the accessibility of the collected data. Medical informatics is developing ways to move from siloed data to a more harmonized arrangement in information architectures. This paradigm shift will allow future research to integrate med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…Data integration has the objective of providing data management methods to create these holistic views (e.g., integrated views of genes, tissues, and tumors). While these interoperability issues are readily apparent in the biomedical field [39], similar issues persist across industrial and scientific domains where data is autonomously generated. The challenge is to provide data management mechanisms that enable seamless data integration while also ensuring scalability and maintainability to guarantee long-term usability and value of the integrated data.…”
Section: Preliminariesmentioning
confidence: 99%
See 2 more Smart Citations
“…Data integration has the objective of providing data management methods to create these holistic views (e.g., integrated views of genes, tissues, and tumors). While these interoperability issues are readily apparent in the biomedical field [39], similar issues persist across industrial and scientific domains where data is autonomously generated. The challenge is to provide data management mechanisms that enable seamless data integration while also ensuring scalability and maintainability to guarantee long-term usability and value of the integrated data.…”
Section: Preliminariesmentioning
confidence: 99%
“…Next, we present the steps involved in declaratively specifying a KG using RML. To ensure the effectiveness of RML engines, we will elucidate the requirements that they need to satisfy, based on existing evaluation studies reported in the literature [15,34,39]. Finally, we will illustrate the problem of KG creation in a use case derived from the data integration challenges in the biomedical area.…”
Section: Declarative Specifications Of Pipelines For Knowledge Graph ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The main functional requirements that represent the necessary boundary conditions for our process ows are outlined in Table 1. These requirements can be derived from the functional requirements for medical data integration into knowledge management environments [29]: Table 1 Main functional requirements for development of the use case agnostic processes.…”
Section: Requirements Analysismentioning
confidence: 99%
“…The integration involved transferring daily CSV reports containing image metadata and radiological reports into the MeDIC's object storage. The CSV reports underwent processing using the platforms ingestion procedures, extracting valuable information, linking patient data through the MPI, and converting the imaging metadata via an ETL job to the standardized openEHR data model [39]. The integrated imaging information and associated data were then stored in the openEHR-based CDR [40].…”
Section: Recontacting Patients In a Radiology Scenariomentioning
confidence: 99%